Method for preparing zeolite object and zeolite object obtained by said method

By using submicron zeolite crystals in the zeolite reaction mixture and subjecting controlled drying and extrusion treatment, the problems of unsatisfactory porosity and low density caused by the use of high-level adhesives in the prior art are solved, and the preparation of high-performance zeolite objects is achieved.

CN119585205APending Publication Date: 2025-03-07IMMATERIAL LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380051405.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-07-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to avoid the use of high levels of adhesives when preparing industrially relevant robust and high-performance zeolite objects, resulting in undesirable porosity, low density, and limited catalytic selectivity and service life.

Method used

By forming a reaction mixture containing submicron zeolite crystals, a controlled water drying step is used to form a partially dried zeolite material and extrusion or cutting on this basis, reducing or eliminating the need for adhesives and increasing the robustness and density of the zeolite object.

Benefits of technology

It is achieved without using high-level adhesives to prepare zeolite objects with improved performance, including high density, tight filling, improved robustness and catalytic activity, extending the service life of zeolite objects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for preparing a zeolite object.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing zeolite objects. Background Art

[0002] The present invention provides for the production of robust and high-performance zeolite objects that are industrially relevant. The term "industrially relevant" refers to a method that uses cost-effective and readily available equipment and is capable of producing several kilograms of zeolite objects per day. Thus, laboratory preparation protocols and procedures for preparing gram-scale samples using, for example, beakers and test tubes are generally not industrially relevant.

[0003] Zeolites are adsorptive inorganic crystalline materials that are used for adsorbing gases or other substances or for many catalytic processes. Zeolites are used as substrates for many catalysts or as catalysts themselves. Zeolite objects can be cation-exchanged or impregnated with a metal substance (such as a metal oxide). The porosity of zeolite objects is clearly important for the zeolite objects to be able to function as catalyst or adsorbent objects. If the porosity of the zeolite objects is insufficient, reagents cannot access the active catalyst sites. If the zeolite objects have too many large pores, the volumetric performance is reduced and unwanted reactants can enter the core of the zeolite objects. Controlling the pore size and porosity level of zeolite objects is clearly important. Zeolites of interest include aluminosilicate zeolites having the chemical formula Na n Al n Si 96–n O 192 ·16H2O (0 < n < 27). Aluminosilicate zeolites having this chemical formula include the widely used catalytic zeolite, commercially known as Zeolite Socony Mobil-5 or ZSM-5. Other useful zeolites also include type A, beta zeolite, titanium silicate-1, faujasite (type X and Y), chabazite (SSZ-13 and SAPO-34), ferrierite, sodalite, and mordenite.

[0004] Zeolites are typically synthesized as fine powders, with an average particle size generally between 2 and 10 microns. They are typically made by a sol-gel process, followed by filtration and washing steps, and then drying. Usually, the crystal size of such zeolites is large enough such that the filtration and washing steps are industrially feasible. Even so, treating, washing, and subsequently separating and drying such fine powders to remove residual reactants or perform ion exchange does incur significant cost and complexity. If these steps could be implemented on larger zeolite objects, it would make handling and separation (such as separating the zeolite objects from wash water) much simpler.

[0005] Zeolites are widely used as carrier media for heterogeneous solid catalysts and other catalytic materials. When used in this manner, usually in a "packed bed", fine zeolite powders need to be formed into larger objects, such as particles with a maximum inner diameter greater than 100 microns or even objects of several millimeters in size, such as extrudates. This method of forming zeolite powders into larger objects improves operability and helps avoid excessive pressure drops and problems that may often occur when using fine powders (such as "channelling"). The use of larger zeolite objects improves fluid flow, thereby helping to improve mass transfer and heat transfer performance under typical industrial process conditions. Zeolite objects need to be strong enough to withstand the conditions of manufacture and use, especially high temperatures and stirring of fluid flows.

[0006] Robustness and strength are important requirements for such zeolite objects. Many industrial processes use such zeolite objects in large "packed beds" and have a fluid (liquid or gas) continuously flow through the packed bed to contact the reactants with the zeolite objects. The fluid may cause the zeolite catalyst objects to move and wear, thereby generating dust. The accumulation of this fine dust material can clog equipment and is one of the main factors limiting the service life of such zeolite objects.

[0007] Zeolite powder is not self-adhesive; therefore it needs to be formed into larger mechanically stable objects of different sizes and shapes. Typically, this requires the use of a binder material at some stage of the process. The binder may be required to provide strength to the "green" article before any drying and / or calcination steps and / or to provide strength to the final formed object. In the context of this application, "green" refers to an object that has not undergone any subsequent calcination steps. If the green body subsequently retains sufficient strength, for example due to sintering, the organic binder can be burned out during the calcination step. The binder can be retained in the zeolite object after formation, or the binder can be chemically converted to other substances in situ. The binder can be an organic material (e.g., an organic polymer) or an inorganic material (e.g., alumina, silicate or clay) and mixtures thereof. Typically in the art, inorganic binder levels of 15% to 30% or more are required to provide sufficient strength and wear resistance for large-scale extended use.

[0008] Another degree of complexity of many zeolites is that they are built around "template" molecules or "structure-directing agents" in order to have a specific size, pore size and shape. These templates are organic molecules and must be removed from the zeolite in order for the zeolite to be functional. This is usually done by calcining the zeolite at temperatures above 500°C after synthesis in order to burn out the template. Obviously, this will also remove any other organic matter that is present. This does not mean that an organic binder cannot be used to help provide green body strength. Some methods use organic binders during the initial processing and rely on sintering of the zeolite particles during the calcination process to provide a strong object.

[0009] Such processes inevitably introduce larger macropores due to burnt-out binder, resulting in objects with lower density and undesirable porosity characteristics. The use of binders such as alumina or boehmite, particularly at relatively high levels required to provide adequate robustness, can also negatively impact parameters of the zeolite object, such as overall zeolite level, porosity characteristics, and chemical properties (e.g., Bromfield acidity). This can occur even if the binder (e.g., silica, alumina, and metakaolin) is subsequently converted to a zeolite by hydrothermal post-treatment or xerogel conversion (so-called "binderless" zeolite objects), since it is likely that 100% conversion of an amorphous material such as metakaolin to a crystalline zeolite will not be possible, resulting in low microporosity. Typically, the zeolite formed by conversion of the inorganic binder in such "binderless" zeolite objects is different from the zeolite from which the zeolite object was formed. Additionally or alternatively, the use of relatively high levels of binder may also result in other negative effects, such as blocking the entrance to the zeolite pores, particularly at the pore openings of the catalyst (causing poorer mass transfer), affecting lower catalytic selectivity and the occurrence of undesirable chemical reactions (e.g., coke formation), and combinations thereof.

[0010] The pore size distribution of a zeolite object can affect catalytic selectivity and life. In particular, controlling and limiting the proportion of larger pores can help control the chemicals that can reach the active catalytic sites. Larger pores, such as mesopores (2nm-50nm) or macropores (>50nm), help allow reactants to enter the catalytic sites located within the inherent micropores of the zeolite crystals. However, larger pores, especially macropores, also allow materials from the catalytic sites (including unwanted chemicals, such as unwanted by-products) to enter and exit too easily. This increases the chance of undesirable reactions occurring. In particular, macropores are often associated with the "coking" problem, in which carbon deposits within the zeolite object accumulate over time and limit performance and the service life of the catalyst.

[0011] Thus, all current zeolite objects are complex compromises between competing and sometimes conflicting requirements. The use of binders to form such objects is necessary, but not desirable, because of the negative effects of the use of any type of binder. An ideal zeolite catalyst object would be one that combines all of the following in a single zeolite object: relatively high robustness, high density, high surface area, high catalytic activity and selectivity, and hierarchical porosity without excessive macroporosity. These requirements are often conflicting.

[0012] Therefore, there is a constant need to develop improved zeolite objects and improved preparation methods to prepare such zeolite objects, particularly strong zeolite objects that require only low levels of binders, or even no binders, throughout the formation process. The inventors have found that if the reaction mixture is dried in a controlled manner to avoid powder production, then the zeolite object is formed and then calcined, a zeolite object with improved performance can be produced directly from a reaction mixture containing submicron zeolite crystals. If these steps are implemented on the powder before the zeolite powder is formed into a larger object, the zeolite object can then be washed and / or ion exchanged in an easier manner than otherwise. Compared to typical zeolite object production by preformed powders, the small zeolite particles in the reaction mixture allow tighter packing in the zeolite object (which increases density and reduces macropores), reduce or even eliminate the need for binder materials, and improve the firmness of the final zeolite object. Even compared to zeolite objects formed from submicron zeolite powders, zeolite objects formed directly from the reaction mixture have improved firmness.

[0013] In order for extrusion or any other zeolite object manufacturing method to be industrially relevant, it must be possible to produce processable extrudates / objects at industrially relevant rates using existing equipment. Much of the prior art disclosed regarding extrusion (or other particle formation steps) of zeolites describes work that has been done on a small scale (e.g., in a laboratory) that may not be easily applicable to industrial processes. Typically, a mixture containing zeolite powder plus a plasticizer / lubricant liquid is made into individual extrudate strands, dried, then chopped, and typically dried and calcined. Very little in the prior art describes the physical properties required for a mixture that is extruded or otherwise formed into an object to achieve large-scale industrially relevant processing. However, successful post-extrusion or general post-production processing of the formed zeolite object is critical to any larger scale productivity.

[0014] For the extrusion process, it is necessary to break or cut the extruded strands into smaller lengths ("extrudates"). This can be done by mechanical cutting or by relying on the breaking of longer extrudates during extrusion and subsequent processing. Extrudates are usually formed by mechanically cutting the extrudate strands using a die face-cutter or using the natural breaking of the strands during subsequent processing. The extrudate is usually cut by a rotating blade moving across the surface of the die sheet. This means that the extrudate can be easily cut into controlled lengths, which can be controlled by the rotation speed of the cutting tool. It may be preferred that such extrudates be cut into various lengths (including small fragments) to help increase the packing density. It is preferred that the extrudate be cut into very consistent lengths.

[0015] In order for the extrudate cutting method or any object forming method based on cutting or grinding action to work, the material should not adhere to any blade / tool ​​used to break or cut the material. If a large amount of material does adhere to the cutting blade / tool, this will quickly lead to the accumulation of material on the cutting tool, resulting in the production of large pieces of material rather than discrete extrudates or objects. Objects (e.g., extrudates) also need not adhere to each other or to the sides of the equipment immediately after cutting or breaking. This is usually a major problem with extrusion cutting processes because the extrudates are concentrated in a small space, resulting in frequent extrudate: extrudate impacts. If the extrudate or object is too soft and / or too sticky, they will adhere to each other after impact. In addition, if the extruded strands are too soft or too sticky, methods that rely on mechanical fracture of the extrudate strands will not work.

[0016] The problem of not having the material adhere to the cutting tool / blade applies to other forms of material besides extrudates, such as thin sheets, thick plates, tablets or other larger objects or substances. Extrudates are a very convenient form, but it is also of industrial relevance to be able to cut or otherwise break other larger objects (such as larger zeolite substances formed by tray drying) into smaller zeolite objects of industrial relevance by using, for example, a slicer or other cutting tool. The formation of smaller zeolite objects is generally followed by optional but highly preferred further processing steps, such as rounding in a spheronizer, controlled drying, calcination, washing, ion exchange and combinations thereof. The calcination step can remove any residual template molecules from within the pores.

[0017] Thus, it can be seen that successful large-scale production of suitable zeolite objects by extrusion or other particle formation methods requires that the zeolite mixture being processed has specific physical properties. Any mixture cannot be too soft when cut or broken, otherwise it will stick to itself or to the sides of the equipment or cutting tools, quickly rendering the process unworkable. If the mixture is too hard, it may be difficult to extrude.

[0018] For clarity, the term "zeolite body" describes an object, such as an extrudate or ground / cut particles (also referred to as a granular object), wherein a majority (ie, > about 50 wt%) of the object comprises one or more zeolites.

[0019] When the zeolite objects are granular objects (e.g. formed by grinding / cutting and sieving), their d 50 The average particle size is preferably greater than about 100 microns to about 3000 microns, such as about 250 microns to about 1500 microns or about 350 microns to about 1200 microns.

[0020] The zeolite bodies of the present invention may also contain catalytic species. Typically, these catalytic materials are present at very low levels and may be incorporated into the zeolite bodies either in the reaction mixture or in a post-formation chemical modification step.

[0021] The present inventors have found that when the zeolite particles / crystals in the reaction mixture used to form the zeolite object have a small size, then an optimized zeolite object is formed. Suitable sizes include zeolite crystals whose d 50 Less than about 1 micron, or less than about 900 nm, or less than about 800 nm, or less than about 600 nm, or less than about 400 nm, or even less than about 200 nm, or most preferably less than about 100 nm.

[0022] It is not easy to separate such small crystals industrially by filtering in the same manner as the larger zeolite particles. Separation, washing and concentration of zeolite particles / crystals from the reaction mixture is usually accomplished in the laboratory by using a high speed centrifuge. This can be done for small zeolite crystals, but is not practical on a large scale industrially due to the cost and complexity of high speed centrifugation.

[0023] It is highly preferred that the zeolite reaction mixture containing these small zeolite particles / crystals is not subjected to a powder-forming drying step (e.g., flash drying or spray drying) to remove water before being formed into larger zeolite objects. Rapid drying processes produce zeolite powders. The production of zeolite powders generally requires the use of high levels of binders to prepare strong zeolite objects, which has negative effects. In addition, such rapid drying steps generally aggregate the small zeolite particles into larger porous powder particles, which causes any resulting zeolite objects to have low mechanical stability and bulk density.

[0024] In the method of the present invention, the zeolite reaction mixture containing small zeolite particles / crystals is typically concentrated by controlled (and slower) removal of water to form a solid or highly viscous paste or gel-like material, rather than a powder, before forming a smaller zeolite object. Such solid or highly viscous paste-like materials are referred to as "partially dried" zeolite materials. Typically, the zeolite crystals in the reaction mixture are not subjected to a washing step before being formed into a zeolite object. On the contrary, the zeolite object is typically washed after formation to remove impurities. This simplifies processing. Typically, smaller zeolite particles / crystals allow for tighter packing and density in the final zeolite object.

[0025] Adding an adsorptive binder powder to a partially dried zeolite material can generally assist in the formation of subsequent zeolite objects, for example by increasing the viscosity of the partially dried zeolite material so that the partially dried zeolite material can be extruded without problems or otherwise more easily formed into smaller objects. Suitable binders can be selected from silica, alumina, aluminosilicates (including zeolites) and clays. Preferably, the adsorptive binder powder is silica. Silica can also be used as a binder, which enhances the strength of the final zeolite object. The level of silica can be less than 15wt% of the zeolite object, which helps to avoid the problem of high binder levels. Lower levels of silica are preferred, for example less than 10wt% or even 5wt% of the zeolite object. Compared to typical prior art, lower levels of binder are achieved by the small size of the zeolite crystals and the formation of the zeolite object directly from the reaction mixture.

[0026] Other zeolite powders may also be incorporated into the partially dried zeolite material, provided that levels are limited (to, for example, less than about 40 wt %, or less than about 30 wt %, or less than about 20 wt %, or less than about 10 wt % of the zeolite object), which helps to avoid some of the negative effects of the zeolite powders. Preferably, the zeolite powder is the same zeolite formed in the reaction mixture. A preferred option is that the adsorptive zeolite powder comprises recycled zeolite object material, typically after a grinding step. It may be preferred that the partially dried zeolite object is size classified and further dried (in any order) after formation and the dried but off-specification material is ground. Grinding the off-specification material prior to calcination increases the ease of grinding.

[0027] Typically, a "partially dried" zeolite material retains sufficient water to render it deformable and extrudable, but if formed into a shaped object, is sufficiently strong to retain its shape when handled. The partially dried zeolite material is formed into a zeolite object by an object forming step (e.g., extrusion and / or cutting). The zeolite object is then subjected to a subsequent processing step selected from the group consisting of washing, chemical modification, drying, calcining, and combinations thereof. The drying step may be integrated with the calcining step.

[0028] The reaction mixture can be dried by various techniques to form a partially dried zeolite material, usually under the condition of avoiding the formation of zeolite powder. The reaction mixture can be dried by heating to a temperature less than about 100°C, or less than about 90°C, or less than about 80°C, or even less than about 70°C. This may take several days, such as more than about 1 day, or about 2 days, or about 3 days, or about 4 days, or even about 5 days. The reaction mixture can be dried by two or more different techniques. A preferred technique is to concentrate the reaction mixture using a wiped film evaporator. The concentrated reaction mixture from the wiped film evaporator can be a partially dried zeolite material, particularly if fully dried, or it can be further dried (e.g., by slow tray drying) to form a partially dried zeolite material, or it can be combined with an adsorptive material (e.g., silica) to form a partially dried zeolite material. Typically, a partially dried zeolite material will retain some "free" water, but a partially dried zeolite material may not have a measurable level of free water. "Free" water refers to that portion of water that can be removed from a material by drying at 35°C for 5.0 hours. Free water is not tightly bound to the material and can affect the rheology of the zeolite material. For example, water incorporated into the zeolite crystal structure is not considered free water. When measuring free water content, sample volumes between 1.0 g and 2.0 g are typically used.

[0029] The physical properties of the partially dried zeolite material are controlled, for example by controlling the free water content in the partially dried zeolite material so that industrially relevant processes (such as extrusion / spheronization) can be successfully used. If the free water content is too high, the zeolite material will be too soft to be processed into zeolite objects. The free water content in the zeolite material can also be characterized by the water activity of the material and the weight loss. The water activity of a material at a given temperature is defined as the ratio of the air humidity in equilibrium with the sample at that temperature to the saturated humidity of the air at that temperature. The higher the free water content, the greater the water activity. Therefore, an upper limit to the water activity of the processable material can also be defined.

[0030] The partially dried zeolite bodies are calcined, usually to remove any template material, increasing their strength. The small particle size of the zeolite crystals enhances the sintering effect of the calcining step. Summary of the invention

[0031] The present invention provides a method for preparing a zeolite object, wherein the method comprises the following steps:

[0032] (a) forming a zeolite reaction mixture, wherein the zeolite reaction mixture comprises:

[0033] (i) submicron sized zeolite crystals; and

[0034] (ii) water;

[0035] (b) removing at least a portion of the water from the reaction mixture to form a partially dried zeolite material;

[0036] (c) extruding and / or cutting the partially dried zeolite material to form partially dried zeolite bodies;

[0037] (d) subjecting the partially dried zeolite objects to one or more further processing steps selected from a rounding step, a drying step, a size classification step and any combination thereof;

[0038] (e) heating the partially dried zeolite object to a temperature above 400° C. to form a calcined zeolite object;

[0039] (f) contacting the calcined zeolite object with water to form a water-exchanged zeolite object;

[0040] (g) subjecting the washed zeolite object to a cation exchange step to form a cation exchanged zeolite object; and

[0041] (h) heating the cation-exchanged zeolite object to a temperature above 200°C to form the zeolite object.

[0042] Preferably, the zeolite crystals can be selected from: ZSM-5; A-type zeolite; beta zeolite (beta aluminosilicate and Sn-Beta); titanium silicate-1; faujasite (X and Y types); chabazite (SSZ-13, Cu-SSZ-13, Fe-SSZ-13 and SAPO-34); ferrierite; sodalite; mordenite; ZSM-11; ZSM-22; ZSM-23; zeolite L; MCM-22; and any combination thereof. Thus, the zeolite object may include ZSM-5; A-type zeolite; beta zeolite (beta aluminosilicate and Sn-Beta); titanium silicate-1; faujasite (types X and Y); chabazite (SSZ-13, Cu-SSZ-13, Fe-SSZ-13 and SAPO-34); ferrierite; sodalite; mordenite; ZSM-11; ZSM-22; ZSM-23; zeolite L; MCM-22; and any combination thereof.

[0043] Step (e) will typically remove any template material from the calcined zeolite body. Step (e) may be performed at a temperature above about 400°C or above about 500°C (e.g., about 550°C). Step (h) may be performed at a temperature above about 200°C (e.g., about 250°C or about 300°C or about 350°C or about 400°C or about 450°C or about 500°C or about 550°C or even higher).

[0044] The adsorptive binder powder may be incorporated into the partially dried zeolite material during step (b) and / or (c). It may be highly preferred to include the adsorptive binder powder into the partially dried zeolite material during or after step (b) to improve step (c). This may simplify step (b) by, for example, reducing the amount of water that needs to be removed.

[0045] The partially dried zeolite material is typically formed into partially dried zeolite objects, such as extrudates of a predetermined length. They are then typically subjected to one or more further processing steps, such as drying, size classification and / or spheronization. The partially dried zeolite object may also be further dried in a secondary drying step. The partially dried zeolite object is calcined to form a calcined zeolite object. Preferably, any drying step, typically step (b) and / or step (d), is carried out under controlled and limited conditions, such as below about 100°C or below about 70°C or even below about 50°C. It may be preferred that when the water content in step (b) and / or step (d) is greater than about 70 wt%, the initial drying step is carried out at a temperature of about 100°C or above about 100°C. It may also be preferred that when the water content in step (b) and / or step (d) is about 70 wt% or less than about 70 wt%, the drying step is carried out at a temperature of less than about 100°C or less than about 70°C or even less than about 50°C. In step (b) and / or step (d), when the material is dried and the water content is reduced, it may be preferred to manage the drying temperature in the manner described above. It may be preferred to combine step (d) and step (e) by making the drying step part of the calcination cycle. Any secondary drying step may also be combined with the calcination step.

[0046] Higher temperatures may be used when the water content of the reaction mixture is high (e.g. initially) but needs to be reduced as the reaction mixture begins to solidify. Controlled drying of the partially dried zeolite material and zeolite object is believed to be important for controlling the macroporosity and mesoporosity of the partially dried zeolite object. The faster the drying, the larger the scale of porosity is introduced into the resulting object. If the drying is too rapid, the zeolite material or zeolite object may even break apart.

[0047] The present invention also provides one or more zeolite objects prepared according to the method disclosed herein, wherein the or each zeolite object comprises greater than 85% zeolite; and wherein the or each zeolite object has an envelope density of 0.6 g / cm 3 Up to 1.4g / cm 3 and wherein the or each zeolite object has a macroporosity of less than 15% as measured by mercury porosimetry.

[0048] The or each zeolite object may be d 50 The zeolite object or each zeolite object may be in the form of particles having a particle size between 100 microns and 3000 microns. The or each zeolite object may be in the form of an extrudate having a minimum internal dimension (thickness) greater than about 100 microns and a maximum internal dimension (length) less than about 10 cm. The or each zeolite object may have a particle size greater than 0.5 g / cm 3 The bulk density. DETAILED DESCRIPTION

[0049] Throughout the specification, one or more aspects of the present invention may be combined with one or more features described in the specification to define different embodiments of the present invention.

[0050] Unless the context implies otherwise, references herein to the singular of a noun encompass the plural of the noun and vice versa.For example, the term zeolite object should be understood to refer also to a plurality of zeolite objects.

[0051] Throughout the specification, the words "comprise / comprises / comprising" will be understood to imply the inclusion of stated elements, integers or steps, or groups of elements, integers or steps, but not the exclusion of any other elements, integers or steps, or groups of elements, integers or steps. The term "comprising" includes within its scope the terms "consisting" or "consisting essentially of".

[0052] The term "consisting of" or variations thereof will be understood to imply the inclusion of stated elements, integers or steps, or groups of elements, integers or steps, and the exclusion of any other elements, integers or steps, or groups of elements, integers or steps.

[0053] The term "consisting essentially of" or variations thereof shall be understood to imply inclusion of the recited elements, integers or steps, or groups of elements, integers or steps, and that other components may be present, but only those that do not materially affect the basic characteristics of the preparation, composition or compound.

[0054] As used herein, when qualifying a number or value, the term "about" is used to refer to a value that is within ±5% of the specified value.

[0055] A method for preparing a zeolite object. The method comprises the following steps:

[0056] (a) forming a zeolite reaction mixture, wherein the zeolite reaction mixture comprises:

[0057] (i) submicron sized zeolite crystals;

[0058] (ii) water;

[0059] (b) removing at least a portion of the water from the reaction mixture to form a partially dried zeolite material;

[0060] (c) extruding and / or cutting the partially dried zeolite material to form partially dried zeolite bodies;

[0061] (d) subjecting the partially dried zeolite objects to one or more further processing steps selected from a rounding step, a drying step, a size classification step and combinations thereof;

[0062] (e) heating the partially dried zeolite object to a temperature above about 400° C. to form a calcined zeolite object;

[0063] (f) contacting the calcined zeolite object with water to form a water-exchanged zeolite object;

[0064] (g) subjecting the washed zeolite object to a cation exchange step to form a cation exchanged zeolite object; and

[0065] (h) heating the cation-exchanged zeolite object to a temperature above about 200°C, or about 300°C, or about 400°C to form the zeolite object.

[0066] The present invention provides a method for preparing a high performance zeolite object from a zeolite reaction mixture comprising submicron zeolite crystals. The zeolite reaction mixture is concentrated by a controlled water drying step to form a partially dried zeolite material. The zeolite material has the form of a solid material or a highly viscous paste-like material, rather than a powder. An adsorptive binder powder can be incorporated into the partially dried zeolite material. A preferred method is to add a low level of adsorbent powder, preferably silica, alumina, aluminosilicate or clay, to the partially dried zeolite material. This can help form the partially dried zeolite object by increasing the green strength of the partially dried zeolite object and / or the ease of cutting the partially dried zeolite material.

[0067] The partially dried zeolite material is then formed into partially dried zeolite objects by extrusion and / or cutting methods. The partially dried zeolite objects are then typically subjected to one or more further processing steps selected from size classification, spheronization, drying and combinations thereof before calcination. The calcined zeolite objects are then subjected to a washing step and very typically to a cation exchange step to remove unwanted cations (e.g. sodium). They are then subjected to a further high temperature treatment step to form the final zeolite objects.

[0068] Zeolite powder may also be incorporated into the partially dried zeolite mass. The zeolite powder may be the same zeolite as the zeolite from which the partially dried zeolite mass is formed or a different zeolite. Preferably, the zeolite powder is a recycled material from a later stage of the process. For example, the zeolite powder may be selected from: ZSM-5; A-type zeolite; β-zeolite (β-aluminosilicate and Sn-Beta); titanium silicate-1; faujasite (X and Y types); chabazite (SSZ-13, Cu-SSZ-13, Fe-SSZ-13 and SAPO-34); ferrierite; sodalite; mordenite; ZSM-11; ZSM-22; ZSM-23; zeolite L; MCM-22; and any combination thereof.

[0069] The process of the present invention is believed to allow the use of lower levels of binder material (eg, less than about 15 wt % of the zeolite body), which minimizes the negative effects discussed above.

[0070] Step (a). Forming a zeolite reaction mixture. Step (a) forms a zeolite reaction mixture.

[0071] Preferably, step (a) is implemented by:

[0072] (i) contacting together:

[0073] (a) zeolite precursor materials, preferably two or more zeolite precursor materials, preferably three or more zeolite precursor materials; and,

[0074] (b) water,

[0075] so as to form a diluted reaction mixture, wherein the diluted reaction mixture comprises:

[0076] (a) submicron sized zeolite particles / crystals; and

[0077] (b) Water.

[0078] In other words, submicron sized zeolite particles / crystals are formed by contacting zeolite precursor materials (eg, two or more, or three or more zeolite precursor materials).

[0079] Submicron size refers to the zeolite crystals having submicron d 50Average particle size. Preferably, the weight average particle size of the crystals is from about 10 nm to about 1000 nm, or from about 10 nm to about 800 nm, or from about 12 nm to about 700 nm, or from about 15 nm to about 500 nm, or from about 20 nm to about 300 nm, or from about 25 nm to about 150 nm. Small crystals generally increase the particle packing in the zeolite object to provide a higher object density and to increase the level of particle: particle sintering during the calcination step. The method for measuring particle size is described in more detail below. The particle size of the zeolite crystals is generally measured in the reaction mixture using dynamic light scattering, but can also be measured in the final zeolite object using SAXS technology. The particle size of the zeolite crystals can be controlled by changing the concentration of the reactants (zeolite precursor material), the temperature of the reaction mixture and the reaction time. Preferably, the reaction is carried out for several days at a lower temperature (e.g., below about 80° C. or below about 70° C.), for example, from about 3 days to about 10 days, preferably about 5 days. For example, the zeolite precursor materials can be contacted together at about 25° C. and then heated at 70° C. for 5 days. Typically, the precursor materials contain "template" molecules that drive the structure and pore size of the zeolite.

[0080] The zeolite precursor material may be, for example, a silica material (e.g., tetraethyl orthosilicate, sodium silicate, colloidal silica, fumed silica, silica gel and / or amorphous silica), an aluminum material (e.g., aluminum oxide, aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum hydroxide and / or aluminum alkoxide), an alkali metal or alkaline earth metal material (e.g., sodium hydroxide, sodium aluminate, potassium hydroxide and / or calcium hydroxide) and / or an organic structure directing agent (e.g., tetraethylammonium hydroxide and / or tetrapropylammonium hydroxide). For example, the zeolite precursor material may be tetraethyl orthosilicate, tetrapropylammonium hydroxide and aluminum sulfate.

[0081] Step (b). Forming a partially dried zeolite material. Step (b) removes water from the zeolite reaction mixture to form a partially dried zeolite material.

[0082] Step (b) can be realized in many ways.Preferably, precise method conditions are not critical.Preferably, the partially dried zeolite material is not a particle.Generally, the partially dried zeolite material is a highly viscous pasty material.The partially dried zeolite material can be a monolithic mass.Without wishing to be bound by theory, it is believed that controlling (e.g., by increasing and / or reducing) the rate of removing water (e.g., by controlling the drying temperature) can avoid the formation of powdered materials.This can be done in a scraped film evaporator, and then the partially dried zeolite material of the obtained is formed into a smaller partially dried zeolite object.Suitable equipment includes the D-Velpac evaporator (D-Velpac Evaporator) from LCI.The zeolite reaction mixture can be allowed to dry in the extended time at a moderate temperature, for example, spread on a flat surface or in a reaction vessel at the same time, to form a partially dried zeolite material, followed by a formation step, for example, cutting in a cutting grinder or a slicer (flaker) or other suitable cutting equipment. For the avoidance of doubt, the partially dried zeolite material, partially dried zeolite object, calcined zeolite object, washed calcined zeolite object, cation exchanged zeolite object or zeolite object may be ground or sliced. After grinding, the ground zeolite may be sieved to obtain the preferred particle size. The drying time may be greater than about 48 hours at a drying temperature of less than about 70° C., or less than about 65° C., or even less than about 60° C.

[0083] The adsorptive binder powder may be added to the partially dried zeolite material during or after drying. This process combination may provide process advantages, such as limiting the amount of water that needs to be removed (which may simplify processing), while enabling the partially dried zeolite material to be more easily formed (e.g., by extrusion) into smaller partially dried zeolite objects.

[0084] Step (b) can occur in different unit operations, for example, in a scraped film evaporator, some water is removed, and then adsorptive binder powder is added in a mixer or extruder. The mixing of partially dried zeolite material and binder powder can be carried out in the same extruder for forming extrudates, or can be carried out in a separate device. A selection can be to mix the adsorptive binder powder with partially dried zeolite material, then extrude or form smaller objects. Suitable equipment includes the Z Sigma Blade Extruder Mixer from Winkworth Machinery Ltd.

[0085] Suitable silicas for use as additional adsorptive material are precipitated silica or fumed silica, preferably fumed silica or a silica suspension. Suitable fumed silicas include those from Inoxia M-5. Suitable precipitated silicas include Evonik's Sipernat series.

[0086] Typically, the partially dried zeolite material is dried for 10 seconds before forming the partially dried zeolite object. -1 and a viscosity of at least > about 4.0×10 5 mPa.s. A preferred embodiment is to make the partially dried zeolite material deformable under pressure and impact so that it can be rounded, for example in a spheronizer. It may be preferred that the partially dried zeolite material is sufficiently dry and hard so that it can be ground in a grinder to form zeolite objects.

[0087] Step (c). Extruding and / or cutting the partially dried zeolite material to form partially dried zeolite objects. Step (c) extrudes and / or cuts the partially dried zeolite material to form partially dried zeolite objects, the size of the partially dried zeolite objects being smaller than the partially dried zeolite material. The choice of equipment obviously depends on the final application. Extrusion is preferred for making larger objects. Suitable equipment includes extruders, such as Caleva Variable Density Extruder. The extrusion step can also be used to incorporate adsorptive adhesive powder into the partially dried zeolite material before forming the partially dried zeolite object. Cutting / grinding equipment (such as the Retsch SM Cutting Mill series) will be suitable for other applications requiring small objects (e.g., granules). Small zeolite objects include zeolite objects (e.g., granules) formed by grinding or d measured by the method described herein. 50 The particle size is greater than about 100 microns to about 3000 microns, such as about 250 microns to about 1500 microns or about 350 microns to about 1200 microns.

[0088] Step (d). Subjecting the partially dried zeolite objects to one or more further processing steps selected from a rounding step, a drying step, a size classification step and combinations thereof. After the partially dried zeolite objects are formed, typically by extrusion or cutting / grinding, the partially dried zeolite objects are typically not yet suitable for a calcination step. They may be rounded in a spheronizer, or may need to be sized before calcination to remove oversized or undersized objects. Step (d) may also include, for example, the following options: further drying the partially dried zeolite objects (e.g., extrudates), grinding the further partially dried zeolite objects, and size classification of the ground further partially dried zeolite objects. Suitable equipment for such a grinding step includes a Retsch SM cutting mill. Selecting only the best sized objects for subsequent calcination can make it easier to recover off-spec materials. The size and properties of the partially dried zeolite objects depend on the application. Larger extrudates are suitable for some applications, while smaller ground particles are more suitable for other applications, as will be clear to those skilled in the art. It is also useful to further dry the partially dried zeolite objects before calcination. Suitable equipment for spheronization include spheronizers from Caleva, such as the Caleva S500.

[0089] Step (e). Heating the partially dried zeolite object to a temperature above 400°C to form a calcined zeolite object. Step (e) activates the partially dried zeolite object, typically by burning off any template material to form a calcined zeolite object. Step (e) also typically sinters the particles partially together to increase the robustness of the final zeolite object. Step (e) is typically accomplished at a temperature above about 400°C (e.g., about 500°C or about 550°C). Typically, step (e) maintains the zeolite object at an elevated temperature above about 500°C for more than about 1.0 hour, or more than about 2.0 hours, or more than about 3.0 hours, or even more than about 4.0 hours.

[0090] Step (f). Contacting the calcined zeolite object with water to form a water-exchanged zeolite object. Step (f) contacts the calcined zeolite object with water. This helps remove soluble residual reactants. Typically, this step is carried out until the pH of the wash water contacted with the calcined zeolite object is between about 7 and about 8.

[0091] Step (g). Subjecting the washed zeolite object to a cation exchange step to form a cation exchanged zeolite object. The calcined and washed zeolite object is typically subjected to cation exchange by contacting the washed zeolite object with an ammonium chloride solution. This allows free cations (e.g., sodium) to be exchanged with ammonium ions. Suitable ammonium chloride solutions include solutions having a concentration between about 0.25 M and about 5 M. Typically, the cation exchange is carried out for at least about 1.0 hour, preferably at least about 1.0 hour to about 14 hours. Typically, the cation exchange is carried out at room temperature or at an elevated temperature (e.g., at about 60°C to about 100°C). The cation exchanged zeolite object is then typically washed. The cation exchange step may be repeated.

[0092] Step (h). Heating the cation exchanged zeolite body to a temperature above about 200°C, or about 300°C, or about 400°C to form the zeolite body. This step typically removes residual water and any ammonium chloride from the cation exchanged zeolite body to form the final zeolite body.

[0093] Binder. Optionally, a binder may be included in the zeolite mass. Preferably, the binder is silica. When used, the binder is typically added at a level of less than about 15 wt % of the zeolite mass.

[0094] The zeolite bodies may also be subjected to post-synthesis modification steps, such as a further ion exchange step or impregnation with one or more metal species selected from the group consisting of Cu, Ag, Mg, Ca, Sr, Ti, Zr, Hf, Zn, Cd, B, Al, Ga, Sn, Pb, Pt, Pd, Re, Rh, V, P, Zn, Sb, Rb, Li, Cs, Ag, Ba, Cr, Mo, W, Mn, Re, Fe, Co, Ni and precious metals.

[0095] Partially dried zeolite material. A partially dried zeolite material is formed in step (b). Generally, it is important to control the rheology of the partially dried zeolite material. The mixture being cut must be sufficiently "solid" if it is to be successfully cut without smearing. One measure of how "solid" a material is is its viscosity. Therefore, generally, it is important that the viscosity of the partially dried zeolite material is above a minimum value. Adding an adsorbent material and / or a binder to the partially dried zeolite material can change the rheology of the partially dried zeolite material and make it more suitable for forming an object.

[0096] In addition, a preferred option is to subject the partially dried zeolite objects to a rounding step (e.g. in a spheronizer) after cutting or breaking. The rounding of the partially dried zeolite objects is preferably performed as a dust reduction step. However, for the extrudates to be rounded, they need to be sufficiently deformable to achieve this. Preferably, if the partially dried zeolite objects are to be rounded, there is an upper limit to the viscosity value of the partially dried zeolite material.

[0097] Thus, in a preferred process of the invention, typically, the partially dried zeolite material is dried within 10 seconds. -1 The viscosity is greater than about 3.0×10 5 mPa.s or greater than about 4.0×10 5 mPa.s or greater than about 5.0×10 5 mPa.s or greater than about 6.0×10 5 mPa.s or greater than about 7.0×10 5 mPa.s or even greater than about 1.0 mPa.s×10 6 mPa.s. The preferred viscosity can be selected based on the nature and design of the cutting and subsequent processing steps. In the preferred method of the present invention, typically, the partially dried zeolite material is dried within 10 s. -1 The viscosity is less than about 3.0×10 6 mPa.s or less than about 2.0×10 6 mPa.s or less than about 1.25×10 6 Viscosity in mPa.s.

[0098] Partially dried zeolite object. A partially dried zeolite object is formed in step (c). The partially dried zeolite object is subjected to further processing steps in step (d). The partially dried zeolite object can have a range of shapes and sizes. The partially dried zeolite object can be a granule, or a rounded pellet or a larger extrudate. When in extrudate form, the partially dried zeolite object typically has a minimum internal dimension (thickness) greater than about 100 microns and a maximum internal dimension (length) less than about 10 cm. The term "internal dimension" describes the length of a straight line drawn from one edge of the object to the approximate normal to the edge on the opposite side of the object without passing through any external surface. These can be determined by optical microscopy techniques or image analysis using a QicPic device. When the partially dried zeolite object is in granular form (such as those prepared from a larger object that has been ground), the size is typically measured by d 50 The preferred d is described by the average particle size as measured by the method described herein. 50 When the particles are spherical extrudates, d 50Typically may be as large as 3000 microns or even larger.Particle size may be measured by laser diffraction using an apparatus such as the Mastersizer 3000 from Malvern Panalytical.

[0099] Calcined Zeolite Object. In step (e) a calcined zeolite object is formed.

[0100] Water and Cation Exchanged Zeolite Object. In steps (f) and (g) a water and cation exchanged zeolite object is formed.

[0101] One or more zeolite objects. In step (h), a zeolite object is formed. The zeolite object comprises a zeolite and an optional binder (e.g., a silica binder). The binder, if present, is less than about 15 wt % of the zeolite object. Typically, the zeolite object has an encapsulation density of about 0.6 g / cm 3 Up to 1.4g / cm 3 between, usually greater than about 1.0 g / cm 3 .

[0102] Zeolite objects can be d 50 The zeolite bodies may be in the form of particles with a particle size between 100 microns and 3000 microns. The bulk density of the zeolite bodies may be greater than 0.5 g / cm 3 .

[0103] Test Method

[0104] Method for measuring viscosity. A suitable device for measuring the viscosity of undried adhesive materials is the Anton Paar MCR 92 Rheometer, which has a 25 mm diameter plate, a 25 degree cone with a gap of 3.0 mm, and is measured at 25°C. Approximately 2 g of sample is placed on the plate, the upper cone is lowered to the target gap distance, excess sample is removed from the sides and the rotational viscosity is measured. Typically, the viscosity is measured at up to 50 s -1 Viscosity is measured over a range of shear rates. For the purpose of this document, the viscosity of a material is measured at 10 s -1 The viscosity is measured at .

[0105] Methods for measuring water activity. The water activity of a material is defined as the fraction of the relative humidity of the atmosphere in equilibrium with the material, i.e., the ratio of the partial pressure of water vapor above the material to the partial pressure of water vapor above pure water at the same temperature. The term "relative humidity" (or RH) is used to describe water in the atmosphere or gas phase in equilibrium with a solid and is expressed as a percentage, where 100% is the relative humidity of pure water in a closed system. Thus, for any material, the water activity value (aw) is defined as %RH / 100.

[0106] Suitable equipment includes the HC2-AW probe connected to a Hygrolab C1 display unit, both from Rotronic Measurement Solutions. The equipment should be set up and operated correctly in accordance with the manufacturer's instructions. The RH of the material is measured by placing a sample of the material within the measurement chamber of the HC2-AW such that >1 / 4 of the available volume is filled with sample, sealing the chamber and allowing the measurement to reach equilibrium as indicated on the display.

[0107] Unless otherwise stated, water activity measurements were made at 25°C.

[0108] Method for characterizing the size distribution of particles in a zeolite object by SAXS. The size distribution of zeolite particles forming a zeolite object can be characterized by SAXS. In principle, in a SAXS experiment, light is scattered due to the contrast in electron density between two phases. On this basis, the size of equivalent spherical particles or particles of other shapes can be calculated. The SAXS intensity at a specific angle depends on the electron density contrast. This also depends on the size of the particles. Large particles scatter at small angles, small particles scatter at larger angles. To generate the measurement results, fragments of the zeolite object are placed on a sample holder. For SAXS, X-rays are generated by synchrotron radiation. One or more data sets are collected to cover the entire range of scattering angles. Kratky instruments can be used to collect small-angle scattering at larger scattering angles (1e-1 to 4e-0 degrees). Bonse Hart instruments can be used to collect small-angle scattering at smaller scattering angles (2.2e-3 to 5e-1 degrees). In this case, the two data sets are combined into a single scan after background subtraction, and the data are subsequently de-smeared. These decontaminated data are then converted into a volume size distribution function through regularization techniques. The volume distribution function is the final output of this process.

[0109] Measurement of zeolite crystal size. The size distribution of zeolite crystals in a reaction mixture can be measured by dynamic light scattering. Suitable equipment includes the NANO-flex II from Colloid Metrix operated according to the manufacturer's instructions. The sample probe can be inserted directly into the reaction mixture. Dilution of the reaction mixture is usually not required.

[0110] d 50 Measurement of average particle size. This may be measured by laser diffraction techniques, using an apparatus such as the Mastersizer 3000 from Malvern Panalytical and operating according to the manufacturer's instructions.

[0111] Bulk Density. The bulk density of a plurality of objects may be measured by completely filling a suitable cylindrical container of known volume and measuring the mass. Those skilled in the art will appreciate that the size of the container is not fixed, as the appropriate size of the container will depend on the size of the object being measured, the inner diameter and height of the container should each be greater than ten times the largest internal dimension of the object. There is no upper limit to the volume of the container, although larger volumes may require very expensive amounts of material to fill them.

[0112] The mass and volume of the empty container are measured. The container is then filled by pouring the zeolite object into the container from 5 cm above the height of the container. The top of the poured zeolite object is flush with the top of the container. The total mass of the container and the contained zeolite object is then measured. The mass of the zeolite object is calculated by subtracting the mass of the empty container from the total mass of the container and the zeolite object. The bulk density is then calculated by dividing the mass of the zeolite object by the volume of the container.

[0113] Methods for measuring encapsulation density

[0114] The encapsulation density of the zeolite objects prepared according to the present invention is generally greater than 0.6 g / cm 3 , or greater than 0.8g / cm 3 , or greater than 1.0g / cm 3 Typically, the encapsulation density of zeolite objects is less than 1.4 g / cm 3 .

[0115] The packing density of an object can be calculated by dividing the weight of the object (in grams) by its packing volume (in mm 3 ) is measured. Encapsulated volume is defined in ASTM D3766 as "the ratio of the mass of the particles to the sum of the volume of the solids in each piece and the volume of the voids in each piece, i.e., within a closely fitting hypothetical enclosure that completely surrounds each piece".

[0116] Depending on the size and nature of the zeolite object, a variety of techniques are used. For larger regular objects (e.g., extrudates, such as those with a diameter > 3 mm), an accurate 3D scanner is used to measure the object volume. Suitable equipment includes the Leica BLK360. The size of well-shaped extrudates can also be measured with calipers, taking multiple measurements for each extrudate and averaging the thickness and length. Multiple (> 25) extrudates need to be measured, so this is a very labor-intensive method.

[0117] The encapsulation density of an object can be measured using a technique based on the Archimedes principle of volume displacement. Encapsulation density can be measured by mercury intrusion. At atmospheric pressure, mercury will not invade internal pores. Therefore, the volume of mercury displaced by the object at atmospheric pressure is the encapsulation volume of the object. Dividing the weight of the sample by this volume gives the encapsulation density.

[0118] The encapsulated volume and density of an object can also be measured using a powder pycnometer (e.g., GeoPyc Model 1360 from Micrometrics Instrument Corp.). If desired, the encapsulated volume measured by these techniques can be used interchangeably with the encapsulated volume measured by mercury intrusion. If there is a conflict between the results, the powder pycnometer method and the mercury intrusion method are preferred.

[0119] Macroporosity

[0120] The macropores of the zeolite object prepared by the present invention preferably account for less than 15% of the zeolite object. Preferably, the macroporosity is less than 12%, or less than 10%, or less than 7%, or even less than 5% of the enclosed volume, as measured by mercury intrusion. IUPAC convention defines macropores as pores greater than 50 nm.

[0121] The macroporosity of the object can be determined by the following method. Mercury porosity values ​​can be measured according to ASTM D4284-12. Suitable equipment for implementing ASTM D4284-12 includes Micromeritics AutoPore VI 9510 from Micromeritics Corp, USA. The surface tension and contact angle of mercury are taken as 485mN / m and 130° respectively. In ASTM D4284-12, mercury is pressed into the pores under pressure. Preferably, a sample capacity of 1 g is used. Preferably, the zeolite object is crushed and sieved between 710 microns and 250 microns, and the sieved material is used.

[0122] According to the Washburn equation, the pressure required to force mercury into the pores of a sample is inversely proportional to the size of the pores. For characterization purposes, all pores are assumed to be cylindrical. The porosimeter increases the pressure of the mercury within the sample holder so that the mercury invades smaller and smaller sample pores. The AutoPore VI will automatically convert the applied pressure to an equivalent pore diameter using the Washburn equation and the contact angle and surface tension values ​​given above.

[0123] The encapsulated volume of a sample can be determined by the volume of mercury displaced at atmospheric pressure. As the applied pressure increases, mercury is forced into the internal pores. Therefore, the % macroporosity of a sample is the volume of mercury intruded into the sample as the pressure increases from 1.001 atm to 292 atm, as a proportion of the volume displaced at atmospheric pressure. Encapsulated volume can also be measured by other techniques.

[0124] Embodiments of the present invention.

[0125] The following are embodiments of the present invention.

[0126] 1. A method for preparing a zeolite object, wherein the method comprises the following steps:

[0127] (a) forming a zeolite reaction mixture, wherein the reaction mixture comprises:

[0128] (i) zeolite crystals having a submicron particle size; and

[0129] (ii) water;

[0130] (b) removing water from the zeolite reaction mixture to form a partially dried zeolite material;

[0131] (c) extruding and / or cutting / fracture the partially dried zeolite material to form partially dried zeolite objects;

[0132] (d) subjecting the partially dried zeolitic objects to at least one further processing step selected from the group consisting of rounding, drying and size classification;

[0133] (e) heating the partially dried zeolite object to a temperature above about 400° C. to form a calcined zeolite object;

[0134] (f) contacting the calcined zeolite object with water to form a washed calcined zeolite object;

[0135] (g) contacting the washed calcined zeolite object with a solution containing ammonium ions to exchange sodium ions in the zeolite with ammonium ions to form a cation-exchanged zeolite object; and

[0136] (h) heating the cation-exchanged zeolite object to a temperature above about 200°C, or above about 300°C (eg, about 400°C) to form the zeolite object.

[0137] 2. The method according to embodiment 1, wherein step (a) is implemented by:

[0138] (i) contacting together:

[0139] (a) zeolite precursor materials, preferably two or more zeolite precursor materials, preferably three or more zeolite precursor materials; and,

[0140] (b) water,

[0141] so as to form a diluted reaction mixture, wherein the diluted reaction mixture comprises:

[0142] (a) submicron sized zeolite crystals; and

[0143] (b) Water.

[0144] 3. The method according to embodiment 2, wherein the zeolite precursor material and water are maintained at a temperature below about 100°C, or below about 80°C, or below about 70°C, or below about 60°C.

[0145] 4. The method according to any one of the preceding embodiments, wherein step (b) is carried out by drying the reaction mixture at a temperature below about 100°C, or below about 90°C, or below about 80°C, or below about 70°C, or even below about 60°C.

[0146] 5. The process according to any one of the preceding embodiments, wherein step (b) is carried out in a wiped film evaporator.

[0147] 6. The method according to any one of the preceding embodiments, wherein an adsorptive binder powder is incorporated into the partially dried zeolite material during any of steps (a), (b) or (c).

[0148] 7. The method according to embodiment 6, wherein the adsorptive binder powder comprises silica, alumina, aluminosilicate, clay and combinations thereof.

[0149] 8. The method according to any one of the preceding embodiments, wherein additional zeolite powder is incorporated into the partially dried zeolite mass.

[0150] 9. The method according to any one of the preceding embodiments, wherein the zeolite is selected from:

[0151] (i) ZSM-5;

[0152] (ii) zeolite A;

[0153] (iii) beta zeolite (beta aluminosilicate and Sn-Beta);

[0154] (iv) Titanium silicate-1

[0155] (v) Faujasite (X and Y types);

[0156] (vi) chabazite (SSZ-13, Cu-SSZ-13, Fe-SSZ-13 and SAPO-34);

[0157] (vii) ferrierite;

[0158] (viii) sodalite;

[0159] (ix) mordenite;

[0160] (x) ZSM-11

[0161] (xi) ZSM-22

[0162] (xii) ZSM-23

[0163] (xiii) zeolite L;

[0164] (xiv) MCM-22; and

[0165] (xv) any combination thereof.

[0166] 10. The method according to any one of the preceding embodiments, wherein step (c) is performed by using an extruder and step (d) comprises using a spheronizer.

[0167] 11. The method according to any one of the preceding embodiments, wherein the partially dried zeolite material is dried within 10 s. -1 The viscosity at 25°C is about 3.0×10 5 mPa.s to about 3.0×10 6 Between mPa.s.

[0168] 12. The method of embodiment 6, wherein the level of adsorptive binder powder is less than about 15 wt % of the zeolite object.

[0169] 13. The method according to any one of the preceding embodiments, wherein a non-zeolitic catalytic material comprising metal ions and metal-based nanoparticles is incorporated into the zeolite body.

[0170] 14. Use of a zeolitic object prepared according to any one of the preceding embodiments in the catalytic processing of hydrocarbons or alcohols.

[0171] 15. A method for preparing a zeolite object, wherein the method comprises the following steps:

[0172] (a) forming a zeolite reaction mixture, wherein the reaction mixture comprises:

[0173] (i) zeolite crystals having a submicron particle size; and

[0174] (ii) water;

[0175] (b) removing water from the zeolite reaction mixture to form a partially dried zeolite material;

[0176] (c) heating the partially dried zeolite material to a temperature above about 400° C. to remove residual organic matter, thereby forming a calcined zeolite material;

[0177] (d) cutting / breaking the calcined zeolite material to form calcined zeolite objects;

[0178] (e) subjecting the calcined zeolite objects to at least one further processing step selected from rounding, drying and size classification;

[0179] (f) contacting the calcined zeolite object with water to form a washed calcined zeolite object;

[0180] (g) contacting the washed calcined zeolite object with a solution containing ammonium ions to exchange sodium ions in the zeolite with ammonium ions to form a cation-exchanged zeolite object; and

[0181] (h) heating the cation-exchanged zeolite object to a temperature above about 200°C, or above about 300°C (eg, about 400°C) to form the zeolite object.

[0182] 16. The method according to any one of the preceding embodiments, wherein the adsorptive binder powder and / or zeolite powder material is incorporated into the partially dried zeolite mass by using an extruder or a Sigma mixer.

[0183] 17. A method according to any of the preceding embodiments, wherein the zeolite body has been subjected to a further ion exchange step and / or an impregnation step such that the zeolite body has been doped with a metal species selected from the group consisting of: Cu, Ag, Mg, Ca, Sr, Ti, Zr, Hf, Zn, Cd, B, Al, Ga, Sn, Pb, Pt, Pd, Re, Rh, V, P, Zn, Sb, Rb, Li, Cs, Ag, Ba, Cr, Mo, W, Mn, Re, Fe, Co, Ni and / or precious metals.

[0184] 18. One or more zeolite objects prepared according to the method of any one of embodiments 1 to 17, wherein:

[0185] the or each zeolite object comprises greater than 85% zeolite;

[0186] and wherein the zeolite object or each zeolite object has an encapsulation density of 0.6 g / cm 3 Up to 1.4g / cm 3 between;

[0187] and wherein the or each zeolite object has a macroporosity of less than 15% as measured by mercury intrusion porosimetry.

[0188] 19. The or each zeolite object according to embodiment 18, wherein the or each zeolite object is d 50 In the form of particles with a size between 100 microns and 3000 microns.

[0189] 20. The or each zeolite object according to embodiment 18 or embodiment 19, having a bulk density of greater than 0.5 g / cm 3 .

[0190] Each reference mentioned herein is incorporated by reference in its entirety, as if each reference were set forth in its entirety herein.

[0191] Although specific embodiments and / or implementations of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention are covered in the appended claims.

[0192] Example

[0193] Embodiments 1 and 2 of the present invention

[0194] Preparation of ZSM-5 zeolite objects

[0195] The zeolite reaction mixture was prepared as follows: All raw materials were laboratory grade reagents from Sigma-Aldrich.

[0196] 72 g of 1 M tetrapropylammonium hydroxide solution (Sigma-Aldrich) and 60 g of 98% active tetraethyl orthosilicate (Sigma-Aldrich) were mixed under ambient conditions to form Solution 1.

[0197] 15 g of 1 M tetrapropylammonium hydroxide solution (Sigma-Aldrich), 0.21 g of NaOH (Sigma-Aldrich), and 6 g of distilled water were mixed under ambient conditions to form Solution 2.

[0198] Al(OH)3 gel was prepared by precipitation. 1.05 g of hydrated aluminum sulfate (Al2(SO4)3:18H2O) (Sigma-Aldrich) was dissolved in 15 mL of distilled water to which 4 mL of 25 wt% ammonia solution was added. This formed a gel material. The reaction mixture was centrifuged at 5000 rpm for 5 minutes in an Avanta J-15 centrifuge, then washed, centrifuged and redispersed until the supernatant was pH 7.4. All washed Al(OH)3 gel was then slowly added to solution 2 under vigorous stirring. The Al(OH)3 gel and solution 2 were then added dropwise to solution 1 under ambient conditions and vigorous stirring to form a zeolite reaction mixture.

[0199] The reaction mixture was kept at a temperature below 70°C under sealed conditions for 5 days to allow crystallization of ZSM-5 zeolite crystals. The zeolite reaction mixture had a solid content of 27% as measured by drying at 100°C. The particle size of the zeolite crystals was less than 100 nm. The zeolite reaction mixture was then poured equally into four separate 60 mL Falcon tubes.

[0200] Embodiment 1 of the present invention

[0201] Two of the 60 mL Falcon tubes were placed in an oven at 140°C for 1 hour and then slowly dried at 50°C for 5 days to form a solid partially dried zeolite material (Example 1). The partially dried zeolite material was strong and could be easily handled without breaking.

[0202] Embodiment 2 of the present invention

[0203] The remaining two tubes were also placed in an oven at 140°C for 1 hour. 5 wt% (based on the zeolite content of the partially dried zeolite material) of fumed silica (Cab-o-Sil) was then added to each Falcon tube and stirred into the zeolite reaction mixture. This caused the reaction mixture to become thicker, unlike the reaction mixture without silica, so that the reaction mixture could be manually shaped into spherical objects.

[0204] The rounded zeolite material from Inventive Example 2 was then dried in a similar manner to Inventive Example 1 and likewise formed a tough partially dried zeolite material which could be easily handled without breaking.

[0205] The partially dried zeolite materials of Inventive Examples 1 and 2 were then calcined in a muffle furnace at 550°C for 6 hours at a heating rate of 1°C / min to form calcined zeolite bodies.

[0206] The calcined zeolite body was then washed with distilled water until the pH of the surrounding water was 7.3. The cation exchange was then performed by contacting the water-exchanged zeolite body with a 1 M ammonium chloride solution at 80° C. overnight. The cation exchange step was repeated using fresh ammonium chloride solution, and the cation-exchanged zeolite body was then washed again with distilled water until the pH of the water was 7.6.

[0207] The cation exchanged zeolite body was then dried at 50°C and calcined again at 550°C for 6 h at a heating rate of 1°C / min in a muffle furnace to produce the final zeolite body.

[0208] Both zeolite object groups (with and without silica) were solid and did not form any visible dust when shaken vigorously in a glass bottle. When tested, the BTE area of ​​the zeolite object material of Example 1 of the present invention was 442 m 2 / g, which exceeds the performance of commercial ZSM-5 zeolite pellets and extrudates known to the inventors. The BET area of ​​the material of Example 2 of the present invention is 422 m 2 / g.

[0209] Comparative Examples

[0210] Comparative Example 1

[0211] 2.7 g of commercially available ZSM-5 powder (Zeolyst CBV 8014) was dispersed in 7.3 g of deionized water. CBV 8014 has a submicron particle size. The slurry matches the concentration (solid content) in the present embodiment. The slurry was dried and calcined in a manner similar to the other embodiments. The calcined object was then not washed or ion exchanged, as these steps have been performed on the zeolite powder. Unlike the present embodiment, the resulting object broke apart and formed visible dust when shaken vigorously by hand.

[0212] Comparative Example 2

[0213] A slurry similar to Comparative Example 1 was prepared except that the pH of the slurry was adjusted to pH 14 by adding 0.1 M NaOH. This was to test whether the pH of the reaction mixture was responsible for the integrity benefit. The slurry was then dried and calcined in a similar manner to the inventive samples. Again, the sample broke apart and produced visible dust when shaken vigorously by hand.

[0214] Comparative Examples 3 and 4 - To demonstrate that the use of high levels of binder with preformed powders still has disadvantages compared to the inventive objects.

[0215] Comparative Example 3

[0216] 3.5 g CBV 8014 was mixed with 1.5 g alpha alumina (XFNano) in 40 mL water and dried and calcined as in the previous example. The BET area of ​​Comparative Example 3 was only 382 m 2 / g, showing the dilution effect of the adhesive, and when vigorously shaken manually in a manner similar to the other examples, the dried object broke apart.

[0217] Comparative Example 4

[0218] 3.5 g of CBV 8014 were mixed with 1.5 g of silica (Sipernat 22S) in 40 mL of water and dried and calcined as in the previous example. The BET area of ​​Comparative Example 4 was only 386 m 2 / g, demonstrating the dilution effect of the adhesive, and the dried object also broke apart when vigorously manually shaken in a manner similar to the other examples.

[0219] Embodiment 3 of the present invention

[0220] A zeolite reaction mixture with a solids content of 50% was prepared in a similar manner to that used in Examples 1 and 2 of the present invention, with partial drying. The reaction mixture with 50% solids was too soft to form extrudates. 5 wt% (based on the zeolite level) of Sipernat 22S was stirred into the mixture. The mixture could now be extruded and dried and calcined in a similar manner to the previous samples.

[0221] Example 4 of the present invention - Preparation of Silicalite-1 zeolite object

[0222] 20 g of tetraethyl orthosilicate (reagent grade, 98%) (Sigma-Aldrich) and 34 g of 1M tetrapropylammonium hydroxide solution (Sigma-Aldrich) were hydrolyzed with stirring overnight at ambient conditions to form a clear solution. 0.63 g of water was added to the clear solution. The clear solution was kept in a sealed Teflon-lined stainless steel autoclave in a preheated oven at 120° C. for 3 days to crystallize the zeolite nanocrystals of Silicalite-1.

[0223] The particle size of the zeolite crystals was about 100 to 120 nm. The colloidal zeolite suspension was poured into a 60 mL Falcon tube and dried at 140° C. for 1 h, then slowly dried at 60° C. for five days to form a solid zeolite object. The zeolite object was calcined at 550° C., washed in distilled water, cation exchanged, dried at 60° C., and calcined at 550° C.

[0224] The BET area of ​​Silicalite-1 zeolite is 506 m 2 / g and will not break or form dust when shaken vigorously.

[0225] Inventive Example 5: Preparation of a zeolite object comprising β zeolite.

[0226] 0.21 g NaOH (97+%, ACS reagent, pellets, Acros Organics) was dissolved in 25.2 g tetraethylammonium hydroxide (35 wt.% in H2O, Sigma-Aldrich) to form Solution 1. 0.17 g aluminum isopropoxide (≥98%, Sigma-Aldrich) was then dissolved in Solution 1 under vigorous magnetic stirring. 33.3 g AS-30 colloidal silica (35 wt.% suspension in H2O, Sigma-Aldrich) was added dropwise to solution 1 under vigorous stirring for 2 h to 15 to obtain a clear solution 1. The clear synthesis solution 1 was statically aged for 48 h at room temperature and heated in a synthesis furnace at 100°C for 6 days. Then 1.13 g of aluminum isopropoxide (≥98%, Sigma-Aldrich) was added to solution 1 and stirred for 2 h at room temperature. The synthesis mixture was heated in a Schott bottle in a preheated synthesis furnace at 100°C for 5 days.

[0227] After the solvothermal treatment, the colloidal zeolite suspension was poured into a 60 mL Falcon tube and dried at 140° C. for 1 h, then slowly dried at 60° C. for 5 days to form a solid zeolite object. The zeolite object was calcined at 550° C., washed in distilled water, cation exchanged, dried at 60° C., and calcined at 550° C.

[0228] The BET area of ​​zeolite beta is 973 m 2 / g. The BET area is very large. The micropore volume calculated from t-plot analysis is 0.20 cm 3 / g. The mesopore volume is 0.339cm 3 / g. The NL-DFT pore size distribution curve shows that the mesopore size ranges from 2 to 16 nm. The object is solid and does not generate dust when shaken vigorously.

[0229] Inventive Example 6: Preparation of Zeolite Objects of Zeolite A

[0230] 0.15 g NaOH (97+%, ACS reagent, pellets, Acros Organics) was dissolved in 10.4 g tetramethylammonium hydroxide (25 wt. % in H2O, Sigma-Aldrich) and 4 g distilled water under vigorous stirring to form Solution 1.

[0231] Solution 1 was divided into solution A (8.55 g) and solution B (6 g). Under vigorous magnetic stirring, 0.85 g of aluminum isopropoxide (≥98%, Sigma-Aldrich) was dissolved in solution A. 3.83 g of AS-40 colloidal silica (40 wt.% suspension in H2O, Sigma-Aldrich) was added to Solution B to form a clear solution.

[0232] Solution A was then added dropwise to solution B under vigorous magnetic stirring. The synthesis mixture was statically aged in a Schott bottle at room temperature for 7 days and heat treated at 90° C. for 24 h in a preheated synthesis furnace.

[0233] After the solvothermal treatment, the colloidal zeolite suspension was poured into a 60 mL Falcon tube and dried at 140° C. for 1 h and slowly dried at 60° C. for 5 days to form a solid zeolite object. The zeolite object was calcined at 550° C., washed in distilled water, cation exchanged, dried at 60° C., and calcined at 550° C.

[0234] The BET area of ​​zeolite A is 483 m 2 / g. The micropore volume calculated from the t-diagram analysis is 0.12 cm 3 / g. The mesopore volume is 0.18cm 3 The NL-DFT pore size distribution curve shows that the mesopore size ranges from 2 to 15 nm.

[0235] Zeolite objects are solid and will not break or form dust when shaken vigorously.

Claims

1. A method for preparing a zeolite object, wherein the method comprises the following steps: (a) forming a zeolite reaction mixture, wherein the reaction mixture comprises: (i) zeolite crystals having a submicron particle size; and (ii) water; (b) removing water from the zeolite reaction mixture to form a partially dried zeolite material; (c) extruding and / or cutting / breaking the partially dried zeolite material to form partially dried zeolite bodies; (d) subjecting the partially dried zeolitic objects to at least one further processing step selected from the group consisting of rounding, drying and size classification; (e) heating the partially dried zeolite object to a temperature above 400° C. to form a calcined zeolite object; (f) contacting the calcined zeolite object with water to form a washed calcined zeolite object; (g) contacting the washed calcined zeolite object with a solution containing ammonium ions to exchange sodium ions in the zeolite with ammonium ions to form a cation-exchanged zeolite object; as well as (h) heating the cation-exchanged zeolite object to a temperature greater than 200° C. to form the zeolite object.

2. The method according to claim 1, wherein step (a) is implemented by: (i) contacting together: (a) two or more zeolite precursor materials; and (b) water, so as to form a diluted reaction mixture, wherein the diluted reaction mixture comprises: (a) submicron sized zeolite crystals; and (b) Water.

3. The method of claim 2, wherein the zeolite precursor material and water are maintained at a temperature below 100°C.

4. The process according to any one of the preceding claims, wherein step (b) is carried out by drying the reaction mixture at a temperature below 100°C.

5. The process according to any one of the preceding claims, wherein at least part of step (b) is carried out in a wiped film evaporator.

6. A process according to any one of the preceding claims, wherein an adsorptive binder powder is incorporated into the partially dried zeolitic material during either step (b) or (c).

7. The method of claim 6, wherein the adsorptive binder powder comprises silica, alumina, aluminosilicate, clay, and combinations thereof.

8. A method according to any one of the preceding claims, wherein zeolite powder is incorporated into the partially dried zeolite mass.

9. The method according to any one of the preceding claims, wherein the zeolite crystals are selected from: (i) ZSM-5; (ii) zeolite A; (iii) beta zeolite (beta aluminosilicate and Sn-Beta); (iv) Titanium silicate-1 (v) Faujasite (X and Y types); (vi) chabazite (SSZ-13, Cu-SSZ-13, Fe-SSZ-13 and SAPO-34); (vii) ferrierite; (viii) sodalite; (ix) mordenite; (x) ZSM-11 (xi) ZSM-22 (xii) ZSM-23 (xiii) zeolite L; (xiv) MCM-22; and (xv) any combination thereof.

10. A method according to any one of the preceding claims, wherein step (c) is performed by use of an extruder and step (d) comprises use of a spheroniser.

11. A method according to any one of the preceding claims, wherein the partially dried zeolite material is dried within 10 s. -1 The viscosity at 25°C is 3.0×10 5 mPa.s to 3.0×10 6 Between mPa.s.

12. The method of claim 6, wherein the level of the adsorptive binder powder is less than 15 wt% of the zeolite object.

13. A method according to any one of the preceding claims, wherein non-zeolitic catalytic materials including metal ions and metal-based nanoparticles are incorporated into the zeolitic body.

14. Use of a zeolitic object prepared according to any one of the preceding claims in the catalytic processing of hydrocarbons or alcohols.

15. One or more zeolite objects prepared according to the method of any one of claims 1 to 13, wherein: the or each zeolite object comprises greater than 85% zeolite; and wherein the zeolite object or each zeolite object has an encapsulation density of 0.6 g / cm 3 Up to 1.4g / cm 3 between; and wherein the or each zeolite object has a macroporosity of less than 15% as measured by mercury intrusion porosimetry.

16. The or each zeolite object according to claim 15, wherein the or each zeolite object is 50 In the form of particles with a size between 100 microns and 3000 microns.

17. The or each zeolite object according to claim 15 or claim 16, having a bulk density of greater than 0.5 g / cm 3 .